Representation and misrepresentation in later Stuart Britain : partisanship and political culture - Knights, Mark (OUP E-Books., 2006)
This book argues that the period from 1675 was the second stage of a 17th-century revolution that ran on until 1720. It traces the development of the public as an arbiter of politics, the growth of a national political culture, the shift towards a representative society, and a political enlightenment rooted in local and national partisan conflict. - ;In this original and illuminating new study, Mark Knights reveals how the political culture of the eighteenth century grew out of earlier trends and innovations. Arguing that the period from 1675 needs to be seen as the second stage of a seventeen.